Does diet influence the development and treatment of endometriosis? - A literature review - Szpyra, Justyna; Gawlik, Łukasz; Jagodowski, Piotr; Golemo, Jagna; Dębińska, Julia; Ostojska, Magdalena; Celichowska, Magdalena; Górska, Magdalena; Dziuba, Gabriela; Bogoń, Aleksandra (Quality in Sport, 2024)
Introduction and objective: Endometriosis is a chronic disease that can cause symptoms that significantly worsen the quality of life of patients. Treatment methods often fail to produce satisfactory results. Therefore, there is growing interest in the potential role of diet in prevention and management of endometriosis. The aim of the review is to analyze available scientific literature on the impact of diet on the development and alleviation of endometriosis symptoms and the possibility of its use in clinical practice. Brief description of the state of knowledge: Both nutrient deficiencies and excesses can affect health, with gene-nutrient interactions playing a key role in disease prevention and progression. Nutrition can alter gene expression and disease susceptibility, making the study of diet's influence on gynecological diseases like endometriosis important. Research suggests dietary changes can improve symptoms and quality of life for patients with endometriosis. Conclusions: This study confirms that consuming or limiting some of the nutrients can reduce the risk of developing endometriosis and alleviate its symptoms. However, there are many contradictions in the research. The role of diet and nutrition in endometriosis still remains an unexplored area that requires further investigation.